2007
DOI: 10.1158/0008-5472.can-07-1661
|View full text |Cite
|
Sign up to set email alerts
|

The Cooked Meat–Derived Genotoxic Carcinogen 2-Amino-3-Methylimidazo[4,5-b]Pyridine Has Potent Hormone-Like Activity: Mechanistic Support for a Role in Breast Cancer

Abstract: The cooked meat-derived heterocyclic amine 2-amino-3-methylimidazo [4,5-b]pyridine (PhIP) is activated by CYP1A2 to the N-hydroxy metabolite, then esterified by acetyl transferase and sulfur transferase into unstable DNA-reactive products that can lead to mutation. The genotoxicity of PhIP has been implicated in its carcinogenicity. Yet, CYP1A2-null mice are still prone to PhIP-mediated cancer, inferring that alternative mechanisms must be operative in tumor induction. PhIP induces tumors of the breast, prosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 44 publications
2
27
0
Order By: Relevance
“…Two published studies have questioned the ability of PhIP to induce oestrogenic responses in breast cancer cells (Evans et al, 2010;Immonen et al, 2009) (Lauber et al, 2004;Lauber and Gooderham, 2007). The ability of PhIP to induce oestrogenicdependent responses is also supported by the work of independent labs (Bennion et al, 2005;Okudaira et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two published studies have questioned the ability of PhIP to induce oestrogenic responses in breast cancer cells (Evans et al, 2010;Immonen et al, 2009) (Lauber et al, 2004;Lauber and Gooderham, 2007). The ability of PhIP to induce oestrogenicdependent responses is also supported by the work of independent labs (Bennion et al, 2005;Okudaira et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Whilst the former studies investigating the hormonelike properties of PhIP were based on cell line models (Lauber et al, 2004;Lauber and Gooderham, 2007), importantly, Okudaira et al,(Okudaira et al, 2013 used transgenic mice to detect in vivo ERα-dependent genomic instability caused by PhIP exposure, supporting the biological relevance of this mechanism. The data generated in the present study support these previous reports and demonstrate that in MCF-7 breast cancer cells PhIP exposure can also drive the deregulation of miRNA expression (Fig.2-3).…”
Section: Discussionmentioning
confidence: 99%
“…Amino-1-methyl-6-phenylimidazo [4,5-b]pyridine (PhIP) is the most abundantly found HCA in the human diet [3]. Several studies have shown that PhIP can induce tumors in breast, prostate and colon tissue [6][7][8] and rodent models [9][10][11][12]. N-Hydroxy derivatives are formed by the oxidation of PhIP by cytochrome P-450 1A2 (CYP1A2) [13].…”
Section: Introductionmentioning
confidence: 99%
“…HCA causes multifold cytotoxic effect, for example metabolism of PhIP leads to ROS production, and PhIP metabolites produce DNA adduct and DNA strand breaks [1][2][3][4]. Breast epithelial cells contain all the machinery to metabolize HCA and the genotoxic effects of these metabolites may lead to breast cancer [1].The prevention of cancer through diet is categorized as one of the most effective ways to reduce cancer incidence [5]. We hypothesized that curcumin may be a potential food additive that may be inhibitory to PhIP-induced carcinogenicity by inhibiting ROS production, DNA adduct formation and DNA strand breaks.…”
mentioning
confidence: 99%
“…PhIP is known for its genotoxic and carcinogenic effects causing several types of cancer, including breast cancer. HCA causes multifold cytotoxic effect, for example metabolism of PhIP leads to ROS production, and PhIP metabolites produce DNA adduct and DNA strand breaks [1][2][3][4]. Breast epithelial cells contain all the machinery to metabolize HCA and the genotoxic effects of these metabolites may lead to breast cancer [1].…”
mentioning
confidence: 99%